Performance of Composite Concrete-Filled Plastic Tubular Stub Columns Under Axial Compressive Loads - Krishna Yadav, Kethumalla Sai; Bhaskar, M. Uday; Reddy, B. Sudharshan (Journal of Neonatal Surgery, 2025)
The development of Concrete Filled Plastic Tube (CFPT) Stub Columns, is commonly used in the areas where the concrete structures interact with marine and saline environments, compared to regular concrete columns. CFPT and Composite CFPT stub column samples were prepared to investigate their behaviour under certain loading conditions. The main objective of this study was to conduct an experimental investigation to observe the effect of using CFPT with and without additional of fibers on the final strength of the concrete columns. In order to achieve this target, three types of loading conditions were applied, including separate load on the concrete, combined load on the concrete and the plastic tube and combined load of composite concrete and plastic tube simultaneously. Comparing and Adding 2% of two different artificial fibers in CFPT columns which are Steel and Polymer fibers. The study revealed a significant improvement in the compressive strength of CFPT Composite CFPT columns with 110 diameters. Overall results show that the use of CFPT columns provides better mechanical performance compared to ordinary concrete columns. An evaluation of using the available calculation methods to predict the load-carrying capacities of CFPT. The study suggested the use of CFPT columns in situations where common concrete may cause significant issues related to its deterioration and disintegration in response to severe weather conditions